Socioeconomic factors affecting postpartum mental health in mothers referred to a hospital in yasuj, Southwestern Iran - Leila Manzouri; Marzieh Karami; Maryam Seyed-Nezhad; Mohammad Moradi-Joo (BMC Pregnancy and Childbirth)
Abstract Background Postpartum mental health is a significant concern for maternal well-being, influencing both the mother and her child. This study aimed to determine the social and economic factors affecting postpartum mental health in mothers referred to a hospital in southwestern (Imam Sajjad, Yasuj) Iran. Methods In this cross-sectional (descriptive-analytical) study. Based on census, all of 120 mothers who had referred to the referral hospital of gynecology and obstetrics of yasuj, southwestern Iran, during a 6-month period in 2024 were studied. To determine mental health status, the Depression, Anxiety, Stress scale 21 questionnaire (DASS21), which is a self-assessment tool for depression, anxiety, and stress, was used. Data were analyzed using ordinal regression in SPSS version 21. Results Mean age of the participants was 25.82 ± 5.93 years. Urban residence (estimate: -1.16, 95% CI: -2.29 to − 0.04), IHIO insurance coverage (estimate: -2.22, 95% CI: -4.37 to − 0.07), rental housing (estimate: 18.08, 95% CI: 17.09–19.06) had a significant effect on maternal depression. Also, rental housing (estimate: -13.32, 95% CI: -14.22 to -12.42) and low-income level (estimate: 1.61, 95% CI: 0.02–3.19) had a significant effect on maternal anxiety. Participants’ age (estimate: 0.10, 95% CI: 0.01 − 0.18), literacy level below high school (estimate: -2.94, 95% CI: -5.80 to − 0.096), employment status (estimate: 4.35–5.018), low-income level (estimate: 2.382, 95% CI: 0.77–3.98), and household head debt (estimate: 0.97, 95% CI: 0.11–1.80) had a significant effect on maternal participants’ stress. Conclusion Given that, several socioeconomic factors can affect the mental health of mothers after childbirth, the necessity of screening of mental health during pregnancy and postpartum must be mentioned and further studies need to be conducted to assess the mental health status of women in preconception counseling. On the other hands, assessing the mental health status with different valid and reliable tools would improve accuracy and allows for comparison of results.